Elderly Patients Are at Greater Risk of Cytopenia During Antiviral Therapy for Hepatitis C - CG Nudo; P Wong; N Hilzenrat; M Deschênes (Canadian Journal of Gastroenterology)
The results of antiviral therapy for hepatitis C virus (HCV) have improved recently with the use of pegylated interferon (PEG-IFN)/ribavirin (RBV) combination therapy. At this point, most patients with chronic HCV remain untreated. Thus, it is anticipated that therapy will be more appealing and prescribed more broadly than in the past, including in patients considered marginal.